Diagnosis or Detour? The Uses of Medical Realism in the Victorian Novel - Kennedy, Meegan (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractThis essay attempts to open up our perspective on novels’ use of medical narrative realism. Previous analyses of “medicine and the novel” have focused on a common realist ideal and on novels with medical content. But even a realist methodology shared by the novel and by medicine did not find common expression in both genres. Accordingly, this paper draws on some examples that are representative of nineteenth-century novels and range from literal discussions of disease to scenes much farther removed from literal depictions of medicine or disease, but which still, I am arguing, draw on narrative techniques associated with medical clinical realism for their effect. In fact, novels revised and redirected such techniques, often using them against the grain of the professional ideology from which they arise. Accordingly, this essay will sketch out not only how medical case histories can use supposedly literary techniques, but also how nineteenth-century novels apply the narrative methods of clinical medicine even where medicine is not strictly at issue, and how they adapt those methods to their own literary aims.